Relevansi Religiusitas Dengan Perilaku Konsumsi - Isnaini, Desi (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2020)
Religiosity in every researchs admitted has related with economic behaviour. Wich related to others or personally. This research discuss about the relevance of religiosity to consumption behaviour, using library research. From this research can be concluded that religiosity will affect consumption behaviour, one of them is consumer behaviour. The more religiosity, then the consumption behaviour applied is the more advantages and the good consumption behaviour.